First record of Tetramicra brevifilum in lumpfish ( Cyclopterus lumpus, L.) - F Scholz; E Fringuelli; M Bolton‐Warberg; M Marcos‐López; S Mitchell; P Prodhol; D Moffet; P Savage; S Murphy O'Sullivan; I O′Connor; E McCarthy; H D Rodger (Journal of Fish Diseases, 2017)
A microsporidian species with 98.3–98.4% nucleotide identity to Tetramicra brevifilum ( Journal of Fish Diseases , 3 , 1980, 495) was diagnosed in lumpfish ( Cyclopterus lumpus , L.) broodstock held at a breeding and rearing facility in western Ireland. The fish were wild‐caught from the west coast of Ireland, and the first case was diagnosed one year after capture. Clinical signs included severe bloating, lethargy, exophthalmos, anorexia, white patches on the cornea and externally visible parasitic cysts on skin and fins. Necropsy revealed severe ascites, white nodules and vacuoles in all the internal organs and partial liquefaction of the skeletal muscle. On histological examination, microsporidian xenomas were observed in all internal organs, the skin, skeletal muscle, gills and the eyes. The microsporidian species was identified by molecular analysis and transmission electron microscopy. This is the first record of T. brevifilum infecting lumpfish, and the disease is considered to be of potential significance to the rising aquaculture industry of this species.